Feasibility study on green transportation. (February 2019) - Todorovic, Milan; Simic, Milan
Abstract: This is a research report on a green transportation project. Green transportation relies on renewable energy sources rather than fossil fuels currently used extensively. Sustainability assumes low impacts on environment and balancing current and future needs. We are investigating introduction of electrical vehicles (EV) and issues which influence that EVs are rapidly becoming a mainstay in vehicle product lines. These issues are related to the remaining available reserves of fossil fuels, important for the further use of Internal Combustion Engines (ICE), from one side, and on the other side, availability and reserves of lithium and other metals, required for EV batteries and motors, which makes impacts on swiftness of green transportation introduction. This transition to EVs is characterized by the convergence of mobility and energy what can bring significant benefits to the entire society. There are also policy implications which direct the usage of green energy for EV charging and development of related infrastructure. Finally, we present the economics of green transportation and business models which ensure its sustainability.